The relationship between working capital management and firm performance - Yusoff, Hanaffie; Ahmad, Kamilah; Ong, Yi Qing; Mohamed Zabri, Shafie (American Scientific Publishers, 2018)
An efficient working capital is important for ensuring good financial health and performance of a firm. The purpose of this paper is to investigate the level of working capital management efficiency and its relationship with firm performance. The secondary financial data were collected from the 2014 annual financial reports of 100 selected manufacturing companies listed in Bursa Malaysia. Multiple regression analysis was carried out to determine whether there is a significant relationship between the components of working capital management and profitability of companies. The result reveals that inventory conversion period, average collection period, and cash conversion cycle are significantly and negatively correlated with profitability. The average payment period is significantly and positively correlated with profitability. Hence, the study provides supports for the significant relationship between a different components of working capital management and profitability. Overall the study suggests that managers can increase the profitability of the firms by improving the efficiency level of working capital management.